Gamer’s loyalty: the role of co-creation value - Arissaputra, Rivaldi; Hurrriyati, Ratih; Dirgantari, Puspo Dewi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study is a type of investigation into the impact of co-creation value on gamer loyalty. This study aimed to analyze the effect of co-creation value on gamers' loyalty in Indonesia. This case study focuses on the Mobile Legend game players in Indonesia. The survey technique used in data collection was a questionnaire with the measurement using an interval scale. The data collection technique used was purposive sampling, with a total of 345 respondents. The analytical method used in this study was carried out using structural equation modeling (SEM) and partial least squares (PLS) with the help of SmartPLS 3.0 software. The findings show that the co-creation value variable affects gamers' loyalty.